Efficacy of Different Pet Treat Formulations to Prevent Infestation by the Mite Tyrophagus putrescentiae - Martinez, Maria A.; Mallie, Jacqueline; Phillips, Thomas W. (My University, 2018)
The pet food industry is a major part of the high-value processed food market in the USA and worldwide. Pest control associated with pet foods is an important activity. The mite Tyrophagus putrescentiae is a prolific cosmopolitan species that can infests high-value pet treats undetected until the infestations increase to very large numbers. Propylene glycol is a food-safe additive used to prevent mite infestations (Zhang et al., 2018; Abbar et al. 2015). Unfortunately, propylene glycol in certain foods can harm pets, and many companies are changing formulations. Here we conducted forced infestation of mites on three experimental pet treats and compared these to the current product that contains propylene glycol for susceptibility to mite infestation. We confirmed that the current product with propylene glycol did not support any mite population growth after a forced infestation with 20 mites. Two of the test formulations showed promise in preventing mite infestation, but one formulation was clearly susceptible to mites.
Keywords: Fall 2018